Comparative efficacy, safety and cost of oral Chinese patent medicines for rheumatoid arthritis: a Bayesian network meta-analysis - Dan Zhang; Jin-tao Lyu; Bing Zhang; Xiao-meng Zhang; Hao Jiang; Zhi-jian Lin (BMC Complementary Medicine and Therapies, 2020)
Abstract Background Rheumatoid arthritis (RA) is a common inflammatory disease with a substantial burden for society and economic worldwide. Chinese patent medicines (CPMs) have gained attention as alternative remedies due to they can exert the satisfactory therapeutic effects via holistic regulation. Currently, several oral Chinese patent medicines are routinely recommended for managing and treating RA. Therefore, a network meta-analysis (NMA), which tries to synthesize evidences for a decision making by evaluating the comparative effectiveness of multiple interventions against the same disease, was undertaken to identify the optimal intervention according to their efficacy in clinical treatment and symptom remission, safety profile and daily cost. Methods Randomized controlled trials (RCTs) regarding CPMs to treat RA were comprehensive retrieved from 3 foreign databases and 4 Chinese databases, and the retrieved results were last updated on January 10, 2019. The bias of the selected trials was assessed by two individuals independently through RoB2. A random-effects model was adopted during the meta-analytic procedures, and outcomes concerning efficacy and safety were evaluated as odds ratios (OR), mean differences (MD) and 95% credible intervals (CI) utilizing Stata 14.1 and WinBUGS 1.4.3 software. Furthermore, the cluster analysis and comprehensive investigation were preformed concerning the comparative efficacy, safety and cost of oral CPMs. Results One hundred sixteen RCTs involving 10,213 individuals met the inclusion criteria and were enrolled into current NMA. The results from existing evidence indicated that Biqi capsule and Yuxuebi capsule probably had a favorable balance in consideration of benefits, tolerability and daily cost. Furthermore, as the least expensive choice, glucosides of Tripterygium Wilfordii tablet was associated with displaying a trend of relieving joint tenderness, joint swelling, and morning stiffness for patients with RA. Conclusion Biqi capsule, Yuxuebi capsule and glucosides of Tripterygium Wilfordii tablet were recommended for treating RA based on the favorable benefits in both clinical efficacy and symptoms, and they, meanwhile, might be associated with the more tolerable and acceptable therapeutic alternative in terms of safety profile and daily cost. Nevertheless, the additional results from high-quality, multi-center and head-to-head trials would be pivotal for supporting our findings.